Identification of Potential Core Genes in Parkinson's Disease Using Bioinformatics Analysis. (18th September 2021) - Quan, Wei; Li, Jia; Jin, Xiya; Liu, Li; Zhang, Qinghui; Qin, Yidan; Pei, Xiaochen; Chen, Jiajun
Abstract : Purpose . This study aimed to explore new core genes related to the occurrence of Parkinson's disease (PD) and core genes that can lead to the progression of PD. Methods . The expression profile data of GSE42966, which contained six substantia nigra tissues isolated from normal individuals and nine substantia nigra tissues isolated from patients with PD, were obtained from Gene Expression Omnibus. Differentially expressed genes (DEGs) were identified, followed by functional enrichment analysis and protein-protein interaction (PPI) network construction. We then identified 10 hub genes and analyzed their expression in different Braak stages. Results . A total of 773 DEGs were identified that were significantly enriched in metabolic pathways. Ten hub genes were identified through the PPI network, namely, GNG3, MAPK1, FPR1, ATP5B, GNG2, PRKACA, HRAS, HSPA8, PSAP, and GABBR2 . The expression of HRAS was different in patients with PD with Braak stages 3 and 4. Conclusion . These 10 hub genes and the metabolic pathways they are enriched in may be involved in the pathogenesis of PD. HRAS may have potential value in predicting the progression of PD.